Leksikon Etnobotani Bahasa Jawa - Suhandono Suhandono; M. Ramlan; Soepomo Poedjosoedarmo; Heddy Shri Ahimsa- Putra (Humaniora, 2004)
Language reflects human conceptualization, human interpretation of the world. This paper describe lexicon ethnobotany in Javanese term of the Javanese speakers' conceptualization/ interpretation of the plants world. In this paper the ethnobotanical lexicons in Javanese are also analyzed in terms of the general principles of ethnobotanical lexicons across languages.